Bounds on the largest Kronecker and induced multiplicities of finite groups. Issue 8 (3rd August 2019) - Pak, Igor; Panova, Greta; Yeliussizov, Damir
Abstract: We give new bounds and asymptotic estimates on the largest Kronecker and induced multiplicities of finite groups. The results apply to large simple groups of Lie type and other groups with few conjugacy classes.